Corporate Governance in Chinese-Listed Companies Going Global. (21st February 2014) - Tomasic, Roman
Abstract: Corporate governance reform challenges Chinese firms trying to establish themselves in global markets. When they enter foreign markets, Chinese enterprises are likely to bring their pre-existing corporate governance practices with them. This article examines how the corporate governance practices of foreign-listed corporations operating in China have been received and how major Chinese companies operating outside China have responded to corporate governance requirements of foreign countries when listing abroad. The pervasive role of the State within individual Chinese companies is fundamental to understanding China's corporate governance practices both at home and abroad. Since the State in China is somewhat fragmented (its various agents operating at the national, provincial, and local levels), large company shares may be held by different state agencies and may be used in different ways. This can result in conflicting obligations to the State. Although China may have copied Western corporate laws, stock market rules, and corporate governance codes, the local meaning of these transplants is inevitably different due to the dominance of the state in large listed companies both as a shareholder and as the regulator. The 'Go Global' campaign of senior Chinese officials might have been expected to consolidate the transposition of corporate governance practice and to have hastened some convergence between Chinese and Anglo-American corporate governance practice. However, this does not seem to have happened as expected. The listing of Chinese companies on foreign stock exchanges does not seem to have resulted in these companies embedding foreign principles of corporate governance.